Pengaruh Penggunaan Media Video Pembelajaran Berbasis Teknologi Terhadap Masalah Perkalian Bersusun pada Siswa Sekolah Dasar - Silnawati, Silnawati; Anwar, Anwar; Ugi, La Eru (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
This study aims to determine the effect of using technology-based learning video media on the problem of stacked multiplication in elementary school students. This study used a quantitative approach with the type of research quasi experiment (Quasy Experiment). The population of this study was also the research sample, namely fourth grade students of SD Negeri 1 Waha Wangi-Wangi totaling 26 students as the experimental class and fourth grade students of SD Negeri 2 Waha Wangi-Wangi totaling 30 students as the control class. Data collection techniques in this study used the administration of descriptive tests (essay) at the beginning and at the end of learning in each sample class. The data analysis technique used Prerequisite Test analysis (Normality Test and Homogeneity Test) and Hypothesis Test. The results of the analysis of this research are the normality test and homogeneity test, showing that the data is normally distributed and homogeneous, then the hypothesis test is estimated using a hypothesis test (independent sample T-test) with the assumption of equal variance. The significance value obtained is 0.000 from tcount = 8.763 > ttable = 2.064. Because the significance value is 0.000 < 0.05; then H0 is rejected and H1 is accepted based on the hypothesis acceptance criteria. Therefore, the researchers concluded that there was a difference in averages so that the use of technology-based learning video media was significantly effective in solving multiplication problems for elementary school students.